The Influence of Project Based Entrepreneurship Education, Income Expectations, and Family Support on Entrepreneurship Interest - Elya Salma Yasmina; Herman Sambodo; Cut Misni Mulasiwi; Lina Rifda Naufalin (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of project-based entrepreneurship education, income expectations, and family support on the entrepreneurial interest of class XII students of SMK Negeri 1 Bulakamba. The background of this study is the low interest of students in entrepreneurship. The method used is a quantitative survey with a sample of 219 respondents through proportional random sampling techniques. The results of this study indicate that project-based entrepreneurship education has a positive and significant effect on entrepreneurial interest; income expectations have a positive and significant effect on entrepreneurial interest; family support has a positive and significant effect on entrepreneurial interest. These findings provide important implications for schools and teachers to continue to develop the quality of project-based entrepreneurship education and improve students' understanding of the potential income from entrepreneurship. Families are also expected to provide support in fostering this interest. Students are expected to be active in participating in entrepreneurial activities, have positive thoughts about business prospects, and be able to convince their families of their choices. This study has limitations, one of which is the use of Google Forms media which requires an internet connection, while some respondents experience access constraints. Researchers help provide connections as a solution. On the other hand, there are other factors outside the research variables that may influence entrepreneurial interest, so further research is expected to add variables to obtain more comprehensive results.